PREVENTION OF DRUG AND SUBSTANCE ABUSE IN SECONDARY SCHOOLS: A CASE OF GARISSA COUNTY, KENYA - Kisaka, Joseph (Advances in Social Sciences Research Journal, 2019)
This paper investigated the prevention of drug and substance abuse in secondary schools in Garissa County of North Eastern Province, Kenya. The research problem emanated from the concern that drug abuse has remained a serious habit in Kenyan schools despite efforts by various stakeholders such as the government, parents, teachers, and religious leaders to reduce it. While this habit continues to cause mayhem among students in secondary schools, studies on its preventive measures particularly in Garissa County remain sunk. Therefore, the study upon which this paper is developed was focused on finding out the existence of drug advisors against drug and substance abuse, examining actions taken by the school administration towards students who abuse drugs, and establishing ways of minimizing drug and substance abuse among students in Garissa County. All the available schools were included in the study sample which comprised of all the 13 head teachers, all the 104 teachers, and 780 students. The information was elicited by use of questionnaires, interviews and focused group discussions. Quantitative data was analyzed through descriptive statistics while qualitative data was presented according to themes. The findings showed that the advisors against drug and substance abuse included religious leaders, parents, teachers as well as guidance and counseling masters. Students were advised during sessions like prayer, opening and closing, assembly, guidance and counseling sessions as well as during the course of administering punishments to students. The existing measures taken in case a student was found abusing drugs and substances of abuse included seeking explanation from parents, administering corporal punishment, suspension from school, as well as taking student to the guidance and counselling master or teacher. Therefore, urgent measures should be put in place in order to save the students from the dangers of drug abuse. Therefore the study came up with measures to curb the vice that included creating awareness in the schools through campaigns against the vice of drug and substance abuse as well as strengthening the department of guidance and counselling in schools and the school administration being more strict in enforcing school rules and regulations. Otherwise students are likely to lose track of their educational careers if such measures are not put in place.